Spectrophotometric determination of single-stranded DNA with self-assembly hairpin DNA and silver nanoparticles. Issue 1 (2nd January 2021) - Zhang, Zhikun; Liu, Qingqing; Ye, Xiaojie; Cao, Yapeng; Hu, Cuixia; Liu, Runjing; Liu, Yumin
Abstract: Nucleic acids containing genetic information are used as biomarkers for the diagnosis of genetic diseases. Herein, silver nanoparticles were utilized as probes to detect single stranded nucleic acids by self-assembly of DNA nanomaterials by spectrophotometry. The target DNA specifically triggered two hairpin DNA molecules to hybridize, generating linear double stranded DNA. This approach effectively prevents silver nanoparticles from aggregating in aqueous solutions of NaCl. Otherwise, silver nanoparticles aggregate without target DNA and hairpin DNA due to the low stability of double stranded DNA. The sensor response was shown to be proportional to the target DNA concentration from 5 to 200 nM with a detection limit equal to 5 nM. This simple platform for the specific determination of nucleic acids without enzymes, labels, and modification and demonstrates great prospects for bioanalysis.